Air pollution, UV irradiation and skin carcinogenesis: what we know, where we stand and what is likely to happen in the future? - Zegarska, Barbara; Pietkun, Katarzyna; Zegarski, Wojciech; Bolibok, Paulina; Wiśniewski, Marek; Roszek, Katarzyna; Czarnecka, Joanna; Nowacki, Maciej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
The link between air pollution, UV irradiation and skin carcinogenesis has been demonstrated within a large number of epidemiological studies. Many have shown the detrimental effect that UV irradiation can have on human health as well as the long-term damage which can result from air pollution, the European ESCAPE project being a notable example. In total, at present around 2800 different chemical substances are systematically released into the air. This paper looks at the hazardous impact of air pollution and UV and discusses: 1) what we know; 2) where we stand; and 3) what is likely to happen in the future. Thereafter, we will argue that there is still insufficient evidence of how great direct air pollution and UV irradiation are as factors in the development of skin carcinogenesis. However, future prospects of progress are bright due to a number of encouraging diagnostic and preventive projects in progress at the moment.